Case Report: Novel Compound Heterozygous RNASEH2B Mutations Cause Aicardi–Goutières Syndrome - Garau, Jessica (Front Immunol, 2021)
Aicardi–Goutières Syndrome (AGS) is a rare disorder characterized by neurological and immunological signs. In this study we have described a child with a phenotype consistent with AGS carrying a novel compound heterozygous mutation in RNASEH2B gene. Next Generation Sequencing revealed two heterozygous variants in RNASEH2B gene. We also highlighted a reduction of RNase H2B transcript and protein levels in all the family members. Lower protein levels of RNase H2A have been observed in all the members of the family as well, whereas a deep depletion of RNase H2C has only been identified in the affected child. The structural analysis showed that both mutations remove many intramolecular contacts, possibly introducing conformational rearrangements with a decrease of the stability of RNase H2B and strongly destabilizing the RNase H2 complex. Taken together, these results highlight the importance of an integrated diagnostic approach which takes into consideration clinical, genetic, and molecular analyses.